Systems engineering : design principles and models - Liu, Dahai (CRC Press, 2015)
For the past several decades, systems engineering has grown rapidly in its scope and application and shown significant benefits for the design of large, complex systems. However, current systems engineering textbooks are either too technical or at a high conceptual level. Written by an expert with more than ten years of teaching experience, Systems Engineering: Design Principles and Models not only gives students exposure to the concepts of systems and systems engineering, but also provides enough technical expertise for them to immediately use and apply what they learn.